THE CREATION OF UMKM GROW THROUGH ASSISTANCE WITH BASIC ACCOUNTING AND MARKETING DIGITALIZATION IN THE MSIB BATCH 6 PROGRAM AT ASOSIASI PENGUSAHA INDONESIA (APINDO) LAMPUNG REGIONAL FOR UMKM GHANIAS CAKE IN BANDAR LAMPUNG - Juandro Pranata Ginting; Chatrine Sopia A.L Tobing; Wira Lorensa (RADJA PUBLIKA, 2024)
Internship Program and Certified Independent Study (MSIB) batch 6 activities at the Indonesian Employers' Association (APINDO) aim to enable UMKM in the Lampung region, especially Ghanias Cake UMKM in Bandar Lampung, to grow and advance in class, as well as support the government's micro, small, and medium enterprise development program. In this UMKM we found several phenomena, including the preparation of financial reports using traditional methods so that the reports produced were incomplete calculation errors often occurred and marketing was still a very conventional strategy marketing so the market was very small. These activity goals are to assist UMKM in making financial reports according to accounting standards and implementing digital marketing to make the market available wider. The implementation method are carried out comprehensively, starting with informing about the problem, providing learning and assistance, from making financial reports, and expanding market areas with online marketing (digital marketing) as an effort to achieve one of the SDGs goals, Decent Work and Economic Growth. This activity's goals are to create widespread and sustainable economic growth and positively impact not only the target community but also the students and universities.